RELEVANSI KEPEMIMPINAN, SUPERVISI DAN KINERJA PADA LEMBAGA PENDIDIKAN - Yudiawan, Agus (Al-Riwayah: Jurnal Kependidikan, 2018)
Principals as leaders are required to maintain the quality of education quality in their institutions. Quality quality can be maintained if good and continuing supervision is carried out. In addition, the choice of lead style is a determining value in implementing quality control to improve the effectiveness of the teacher's performance. This study aims to determine the relevance of leadership, supervision and performance in educational institutions. This article is the result of library research. The data of this study were collected through reading text, theory and relevant research and then analyzed by descriptive-verification method. The results of the study concluded that there was a link between leadership and supervision with teacher performance. The principal as the school leader is obliged to regulate and determine administrative functions including the supervision function with various options such as authoritarianism, democracy or lazzie fire. To the school as a supervisor in supervising the performance of the teacher it will be successful if the headmaster pays attention to the results achieved and treats the teacher well.